GABA-induced current and circadian regulation of chloride in neurones of the rat suprachiasmatic nucleus - Wagner, Shlomo (Blackwell Science Inc, 2001)
1. We have shown previously that GABA, the main neurotransmitter in the suprachiasmatic nucleus (SCN), has dual effects on SCN neurones, excitatory during the day and inhibitory at night. This duality has been attributed to changes in [Cl(−)] (i) during the circadian cycle. To unravel the processes underlying these changes we investigated the biophysical properties of the GABAergic receptors and the regulation of [Cl(−)] (i) in SCN neurones. 2. We used voltage-clamp methodology in conjunction with local application of GABA to characterise the current induced by GABA in SCN neurones within acute brain slices. This current, mediated via GABA(A) receptors, shows moderate voltage dependence, does not desensitise and can significantly alter [Cl(−)] (i). 3. Loading or depletion of intracellular Cl(−) was induced by a train of GABA pulses. The recovery of intracellular Cl(−) was deduced from the change in [Cl(−)] (i) calculated from the response to a test GABA pulse presented at different intervals after the conditioning train of GABA application. The time course of recovery was described by an exponential curve. Recovery following Cl(−) depletion was slower than recovery from Cl(−) loading and was further delayed during the subjective night. 4. We concluded that: (a) SCN neurones express a large number of somatic GABA(A) receptors, which give rise to a modifiable, tonic Cl(−) conductance that modulates cell excitability; (b) two Cl(−) transport mechanisms operate in SCN neurones, one that replenishes the cell with Cl(−) following Cl(−) depletion and another that removes Cl(−) after Cl(−) loading; (c) the efficiency of the replenishing mechanism is reduced during the subjective night; and (d) this reduction explains a lower [Cl(−)] (i) during the night phase of the circadian cycle.